La gestion dérogatoire : une stratégie associant péniblement l’État et les communautés locales dans le Parc National du Haut Niger (Guinée) - Diallo Mamadou Saïdou; Yamna Djellouli (VertigO)
This paper presents the derogatory strategy of management implemented by the Guinean State to integrate traditional structures in the management of the High Niger National Park. Contrary to the traditional management form founded on an exclusive management by State structures, the experiment presented in this paper is based on the traditional structures whose ancestral knowledge is mobilized for a concerted management of natural especially resources fauna and flora. Field observations and investigations reveal that, in spite of the recognition of the role of concerned local communities, they adhere to derogatory management without strong conviction, more especially as the public structures associated to the Park management do not have sufficient means to intervene in an efficient way. This example illustrates the difference between the dominant point of view which preaches the integrated management of protected areas, and the concrete difficulties related to the implementation of such a management system supposed to associate State and traditional communities. Nevertheless, these difficulties should not lead to reject the derogatory management, because our observations and our investigations suggest that the strategy can improve its effectiveness if efforts are made especially to support local community development by income-generating activities for these local populations which put their knowledge at the service of the management of the Park, in one word sustainable développement.